“I’m telling you to stop’: Staging the drama of rape, experiment and sexual consent in Ann Quin’s Three and Muriel Spark’s The Driver’s Seat - Nell Osborne (Angles)
This article considers experimental literary strategies alongside depictions of male sexual violence in work by two British women writers: The Driver’s Seat by Muriel Spark (1970) and Three by Ann Quin (1966). It reframes these novels’ particular interest in staging the drama of rape as literary experiment alongside the feminist struggle to articulate and theorise women’s restricted agency in the context of sexuality. I consider how violent avant-garde aesthetic convention is negotiated through emerging feminist anxieties and meditations on sexual violence and gender in these texts. I will suggest that sexual consent emerges as a paradoxically useful site through which women’s contingent and often precarious status as free and equal subjects is revealed. By staging narrative, temporal and affective experiment into the legal and cultural judgments that establish sexual consent, Spark and Quin deploy a modified aesthetics of shock and transgression, which helps to disclose the discursive limitations of both female agency and victimhood.